THE INFLUENCE OF THE WORK ENVIRONMENT ON THE WORK MOTIVATION OF MUHAMMADIYAH HIGH SCHOOL TEACHERS IN MAKASSAR CITY - Ismail, Muh. Ilyas; Wahidah, Wahidah; Getteng, Abd. Rahman (Program Pascasarjana, UIN Alauddin Makassar, 2021)
This study discusses the influence of the work environment on the work motivation of Muhammadiyah high school teachers in Makassar City with the aim of examining the reality of the Muhammadiyah high school work environment in Makassar City, examining the reality of work motivation of Muhammadiyah high school teachers in Makassar City and examining the effect of the work environment on motivation. Muhammadiyah high school teacher work in Makassar City. This research is classified as quantitative research with ex post facto method. The data collection technique used is a questionnaire while the analysis technique used is descriptive statistics and inferential statistics with simple regression analysis. The results of this study indicate the reality of the working environment of Muhammadiyah high school in Makassar City from the results of data analysis the percentage of 77,4% of the expected criteria, the reality of work motivation of Muhammadiyah high school teachers in Makassar City from the results of percentage data analysis of 76,6%, and there is an influence positive and significant relationship between work environment and work motivation of Muhammadiyah high school teachers in Makassar City is 49,3 %. So it can be concluded that the work environment is one of the factors that influence the work motivation of teachers. The implication of this research is that the school should be able to create a conducive work environment by fulfilling all the learning facilities and infrastructure needed by teachers in learning activities and in supporting the work of teachers so that each teacher can concentrate on carrying out their duties.